Effects of layer thickness in laser-powder bed fusion of 420 stainless steel - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose The purpose of this paper is to investigate effects of layer thickness on densification, surface morphology, microstructure and mechanical and corrosion properties of 420 stainless steel fabricated by laser-powder bed fusion (L-PBF). Design/methodology/approach Standard specimens were printed at layer thickness of 10, 20 and 30 mu m to characterize Archimedes density, surface roughness, tensile strength, elongation, hardness, microstructural phases and corrosion performance in the as-printed and heat-treated condition. Findings Archimedes density slightly increased from 7.67 +/- 0.02 to 7.70 +/- 0.02g/cm(3)and notably decreased to 7.35 +/- 0.05 g/cm(3)as the layer thickness was changed from 20 mu m to 10 and 30 mu m, respectively. The sensitivity to layer thickness variation was also evident in properties, the ultimate tensile strength of as-printed parts increased from 1050 +/- 25 MPa to 1130 +/- 35 MPa and decreased to 760 +/- 35 MPa, elongation increased from 2.5 +/- 0.2% to 2.8 +/- 0.3% and decreased to 1.5 +/- 0.2, and hardness increased from 55 +/- 1 HRC to 57 +/- 1 HRC and decreased to 51 +/- 1 HRC, respectively. Following heat treatment, the ultimate tensile strength and elongation improved but the general trends of effects of layer thickness remained the same. Practical implications Properties obtained by L-PBF are superior to reported properties of 420 stainless steel fabricated by metal injection molding and comparable to wrought properties. Originality/value This study successfully the sensitivity of mechanical and corrosion properties of the as-printed and heat-treated parts to not only physical density but also microstructure (martensite content and tempering), as a result of changing the layer thickness. This manuscript also demonstrates porosity evolution as a combination of reduced energy flux and lower packing density for parts processed at an increasing layer thickness.
Keywords: Layer thickness; Laser-powder bed fusion; Stainless steel; Ultimate tensile strength; Corrosion; MECHANICAL-PROPERTIES; MELTING SLM; MICROSTRUCTURE; CORROSION